Influence of Emerging Technologies on the Utilization of Plant Proteins - Sá, Amanda Gomes Almeida; Laurindo, João Borges; Moreno, Yara Maria Franco; Carciofi, Bruno Augusto Mattar (Frontiers in Nutrition, 2022)
Protein from plant sources is claimed alternatives to animal sources in the human diet. Suitable protein sources need high protein digestibility and amino acid bioavailability. In terms of protein functionality and food applications, they also need high-quality attributes, such as solubility, gelling, water- and oil-holding capacities, emulsifying, and foaming. Thermal processing can improve the nutritional quality of plants with some disadvantages, like reducing the assimilation of micronutrients (vitamins and minerals). Emerging technologies - such as ultrasound, high-pressure, ohmic heating, microwave, pulsed electric field, cold plasma, and enzymatic processes - can overcome those disadvantages. Recent studies demonstrate their enormous potential to improve protein techno-functional properties, protein quality, and decrease protein allergenicity. However, the literature lacks a broader evaluation, including protein digestibility, industrial-scale optimization, and exploring applications to these alternative protein sources.